Acceptability of yoghurt from goat's milk - Olvido, Maria Theresa Buenvenida (1996.)
Yoghurt was produced from fresh goat's milk with lactobacillus bulgaricus, lactubacillus acidophilus and streptococcus thermophilus as starter cultures.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Yogurt; Goat milk; Milk